FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PERNIKAHAN USIA DINI TERHADAP REMAJA PUTRI - Pohan, Nazli Halawani (Jurnal Endurance, 2017)
The early-age marriage is a marriage which done under reproductive age, <20 years old. Riskesdas (2013) stated that among the women at 10 â 54 years old, 2,6 % got marriedbefore 15 years old and 23,9 % at 15-19 years old. Based on the data from Religious Affairs Office (Kantor Urusan Agama) in Kecamatan Na IX-X, there were 83 teenage girls got married at <20 years old in 2015. The purpose of this study is to identify the factors which have correlation with early-age marriage on teenage girls in Kecamatan Na IX-X Kabupaten Labuhan Batu Utara in 2016. This is an analytic study with Case Control design. The results for every variables are; knowledge (p=0,0005), education (p=0,0005), jobs (p=0,0005), economic status (p=0,003), parentsâ role (p=0,270), culture (p=0,001), promiscuity (p=0,001) and mass media (p=0,045), and the multivariate analysis showed that knowledge has p=0,001; OR= 5,082 (95% CI; 1,881-13,732).Â  It can be concluded that there is no correlation between parentsâ role and early-age marriage, and there are some correlations between knowledge, education, jobs, economic status, culture, promiscuity and mass media with early-age marriage, and the dominant factor is knowledge.Â